Network architecture as internet governance - Francesca Musiani (Internet Policy Review, 2013)
The architecture of a networked system is its underlying technical and logical structure, including transmission equipment, communication protocols, infrastructure, and connectivity between its components or nodes. This article introduces the idea of network architecture as internet governance, and more specifically, it outlines the dialectic between centralised and distributed architectures, institutions and practices, and how they mutually affect each other. The article argues that network architecture is internet governance in the sense that, by changing the design of the networks subtending internet-based services and the global internet itself, its politics are affected – the balance of rights between users and providers, the capacity of online communities to engage in open and direct interaction, the fair competition between actors of the internet market.
Keywords: 300; Internet architecture; Internet governance; Decentralisation